Penerapan Perilaku Hidup Bersih dan Sehat di Kelurahan Cinta Raja - Sri Handayani; Diah Kartika Ramdhani; Dewi Tri Rahayu; Apriyani Pusvita Sari; Dina Apriliani; Izzatinisa Izzatinisa; Euis Nandini Adrisa; Dinda Putri Lestari; Putri Serli Pratami; Raden Nugraha; Firza Salsabila; Della Serliani; M. Arafi Maldini; Cien Wulansari (JURNAL PENGABDIAN KADER BANGSA, 2026)
Clean and Healthy Living Behavior (PHBS) at the household level is an important indicator in improving public health status. However, its implementation still faces various environmental and behavioral challenges. This community service activity aimed to analyze factors related to the implementation of PHBS at the household level in Cinta Raja Village. The method used was a quantitative approach with an analytic survey design through a Community Self Survey (Survei Mawas Diri/SMD) involving 100 household heads selected using purposive sampling technique. Data were collected using structured questionnaires and analyzed descriptively using frequency distribution and percentages. The results showed that the lowest PHBS indicators included the presence of mosquito larvae (49%), poor household environmental cleanliness (40%), and uncovered waste containers (39%). These findings indicate that environmental factors are the dominant factors influencing the implementation of PHBS in the community.